Accuracy of CT Cisternography in the Diagnosis of Cerebrospinal Fluid (CSF) Rhinorrhea - Ahsan, Sania; Joarder, Aliuzzaman; Rahman, Yeasmina; Moonmoon, Mahbuba Azim (Journal of Bangladesh College of Physicians and Surgeons, 2026)
Background: Cerebrospinal fluid (CSF) Rhinorrhea refers to the leakage of CSF into the nasal cavity. Accurate detection and precise localization of the leak are essential for effective management and prevention of serious complications such as meningitis and brain abscess. Small or pinhole defects pose a particular diagnostic challenge. Methods: This retrospective cross-sectional study was conducted from February 2016 to January 2024 and included 80 patients with clinical suspicion of CSF Rhinorrhea who underwent CT cisternography at a tertiary care hospital. High-resolution paranasal sinus CT scans were performed following intrathecal administration of iodinated contrast material. Demographic characteristics, CSF leak type, and anatomical location were analyzed using descriptive statistics. A CSF leak was considered present when direct contrast extravasation or opacification of nasal packs was demonstrated on imaging. Results: Of the 80 patients evaluated, CT cisternography demonstrated active CSF leakage in 53 patients. A marked female predominance was observed (75.5%), with most patients belonging to the 41–60-year age group. Spontaneous CSF leaks were more common than traumatic leaks (81.1%), and the cribriform plate was the most frequently involved site (67.9%). Surgical confirmation was available for all CT-positive cases, supporting the accuracy of CT cisternography in localizing active CSF leaks in this subgroup. Conclusion: CT cisternography is a valuable imaging modality for detecting and localizing CSF rhinorrhea in patients with active leaks and plays a vital role in guiding surgical management. Although high diagnostic performance was observed in surgically confirmed cases, cautious interpretation is warranted due to methodological limitations. The observed demographic patterns and leak characteristics provide clinically relevant insights that may assist in targeted diagnostic evaluation and management. J Bangladesh Coll Phys Surg 2026; 44: 3-10